PENGEMBANGAN PENILAIAN PEMBELAJARAN BERBASIS GAMES EDUKASI KAHOOT UNTUK MENINGKATKAN BERPIKIR KRITIS PADA MAPEL IPAS KELAS V SDN 02 JATIREJO KABUPATEN KENDAL - Karimah , Nurani; Yulianto, Sigit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to develop learning assessments using the Kahoot educational game and determine the increase in students' critical thinking skills in the science and science subject of the independent curriculum. The method used in this research is the Borg and gall model. The data obtained was calculated using a Likert scale, normality test, N-gain test to determine the feasibility of the data. The results of the validation test on the material obtained a percentage of 88% and the validation test on the media obtained a percentage of 90%. This can be categorized as "Very Eligible". Based on research and data processing of the normality test with a sig of 0.05, it was found that the average increase in pretest questions was 32.7 and posttest 82.3, there was an increase in scores of 51.1% in the normal distribution category. This is also an assessment of the teacher's response to the use of Kahoot educational games getting a percentage of 95% and student responses to the use of Kahoot educational games getting 92% "Very Appropriate". It can be said that Kahoot educational games can improve student learning. After carrying out the normality test, it is known that student learning outcomes can improve critical thinking skills in the Science and Technology subject, tested using N-Gain, the data results obtained are an ideal score of 100 with an N-gain score of 0.75 which can be categorized as high. It can be concluded that the use of Kahoot educational games as a learning assessment is very practical and effective in learning